Quantification of thermal environments and comfort expectations of residents in hostel dormitories during hot and humid days in Indian composite climate. Issue 1 (2nd January 2022) - Kumar, Sanjay; Mathur, Anuj; Kukreja, Rajeev; Bagha, Ashok Kumar
ABSTRACT: Improved quality of the thermal environment in hostel buildings will have a constructive role in the health, learning and overall productivity of student's activities. We, therefore, conducted a thermal comfort field study in two mid-rise naturally ventilated (NV) hostel buildings during rainy days (August–September, 2018). The field study conducted for three consecutive weeks collecting 642 valid subjective responses (out of 679 sample) with objective information of thermal environments in 253 rooms at different floor levels. Statistical analysis of measured thermal variables was performed for assessing the effects on student's thermal perception considering inter buildings effects, different weather conditions and different daytime duration, respectively. The study reported higher comfort bandwidth of 25.2–33.3°C for the studied group. Results of present study are compared with Predicted Mean Vote (PMV), Predicted Mean Vote with expectancy factor (PMVe) and adaptive Predicted Mean Vote (aPMV). aPMV is observed to be more reliable than PMV and PMVe to estimate the actual thermal sensation of occupants. Further, field study results are showing good agreement with the adaptive comfort models for NV buildings in India. Highlights Study quantifies thermal environments of two multi-storey NV hostel buildings. About 76% responses voted comfortable (±1 TS scale). Comfort bandwidth for occupant's ranges between 25.2–33.3°C for the study period. aPMV model of thermal comfort predicts TS more closely than PMV or PMVe model. Indian composite climate-specific adaptive models fit better with present data base.